A Study on Buyers Purchase Behaviour Towards Herbal Cosmetics in Malappuram District - Anandan , A.P.; Mol , Dr.K.K. Saritha (International Journal of Accounting and Economics Studies, 2025)
Purpose: This study aims to investigate consumer purchasing behaviour for herbal cosmetics in Malappuram District. It focuses on key factors such as environmental awareness, price perception, and product. quality and brand image, to provide insights that support marketers and cosmetic companies in promoting sustainable consumption.Method:A quantitative research approach was adopted, collecting data through a structured survey of 384 respondents. Statistical analysis was conducted using SPSS and AMOS to test hypotheses and establish relationships between the identified factors and consumer behaviour.Results: According to the research, brand image (β = 0.903, p < 0.05), product quality (β = 0.865, p < 0.05), & environmental awareness (β = 0.690, p < 0.05) all have a favourable impact on customer purchasing behaviour, highlighting their significance as major motivators. Conversely, price perception (β = -0.177, p < 0.05) negatively affects purchase behaviour, indicating that higher perceived prices act as a barrier. A significant gender-based difference in purchase behaviour was also identified.Conclusion: The study highlights the critical role of environmental awareness, quality, and brand image in shaping consumer behaviour towards herbal cosmetics. Companies can leverage these insights to develop effective branding, pricing, and sustainability strategies, thereby enhancing consumer trust and promoting sustainable consumption.